2n√(x+1)2+3n√1−x2+n√(1−x)2=0Ta thấy: x=-1 ko là nghiệm ptChia cả 2 vế cho n√(x+1)2 ta đc:2+3n√1−xx+1+n√(1−xx+1)2=0đặt n√1−xx+1=a=> pt: 2+3a+a2=0<=> a=−1 V a=−2+) n>0 => pt vô nghiệm+) n<0∗ a=−1=> 1−xx+1=−1=> 1−x=−x−1=> 0x=2 (vô lí)∗ a=−2=> 1−xx+1=(−2)n=> 1−x=(−2)n.(x+1)=> 1−x+2n.x=(−2)n=> x(2n−1)=(−2)n−1=> x=(−2)n−12n−1ĐÚNG THÌ VOTE VÀ CLICK V NHÉ, SAI ĐỪNG BÁO CÁO NHÉ, :P
2n√(x+1)2+3n√1−x2+n√(1−x)2=0Ta thấy: x=-1 ko là nghiệm ptChia cả 2 vế cho
n√(x+1)2 ta đc:
2+3n√1−xx+1+n√(1−xx+1)2=0đặt
n√1−xx+1=a=> pt:
2+3a+a2=0<=>
a=−1 V
a=−2+) n
chẵn=> pt vô nghiệm+) n
l
ẻ∗ a=−1=>
1−xx+1=−1=>
1−x=−x−1=>
0x=2 (vô lí)
∗ a=−2=>
1−xx+1=(−2)n=>
1−x=(−2)n.(x+1)=>
1−x+2n.x=(−2)n=>
x(2n−1)=(−2)n−1=>
x=(−2)n−12n−1ĐÚNG THÌ VOTE VÀ CLICK V NHÉ :P